SPIRITUALITAS MASYARAKAT MODERN DALAM TASAWUF BUYA HAMKA - Nur Azizah; Miftakhul Jannah (UIN Raden Mas Said Surakarta, 2022)
Hamka's modern Sufism is very important for this modern era, because modern society is now trapped by a rational mindset and leaves the spiritual dimension, giving birth to a materialistic and dry lifestyle of spiritual values. This paper aims to examine the role of spirituality which is an important part of Hamka's Sufism as an alternative solution to the current humanitarian crisis. This type of research is library research, namely research through literature review or literature that presents material related to the research theme in the form of books, journals and reports from previous research results. In his modern Sufism, Hamka wants to interpret Sufism which is an old scientific discipline with a modern meaning, which is relevant today as an effort to make happiness in modern society dry from spiritual elements. Because the essence of Sufism according to Hamka is the purification of the soul and avoidance of desires, misery, and something bad. Hamka's modern Sufism thinking is very important and deserves to be used as a reference for the world today, because society has been influenced by materialistic Western traditions, in the sense that Muslim communities only think and act on worldly aspects compared to the hereafter